Copper wire bonding process after copper treatment of silicon carbide power device chip
By adopting the copper-wire bonding process on the silicon carbide power device chip, the problem of difficult control of the thickness and uniformity of the coating layer in the preparation of the chip electrode layer is solved, more stable electrical connections and higher damage resistance are achieved, and the reliability and service life of the chip are significantly improved.
Patent Information
- Application Number
- CN202411795283.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art is difficult to accurately control the thickness and uniformity of the coating layer when preparing the chip electrode layer, resulting in wafer warping or insufficient buffering, affecting chip reliability; insufficient optimization of traditional bonding technology parameters leads to unstable bonding quality and frequent occurrence of dummy welding and desoldering; the stress buffering effect of conventional buffer layers is poor, which limits the chip's damage resistance and overall stability improvement.
The copper wire bonding process after copperization of silicon carbide power device chips is adopted, including chip pretreatment, electrode layer evaporation, preparation of gradient structure buffer layer, copper wire preparation and hot pressing ultrasonic bonding, etc., to improve bonding quality and stress dispersion effect by precisely controlling the thickness and structural design of the plating layer.
The stability and bonding quality of the chip surface electrical connection are improved, which significantly improves the reliability and damage resistance of the chip, extends the service life of the chip, and reduces the risk of product failure caused by chip damage.
Smart Images

Figure CN119694909A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chip manufacturing, and in particular to a copper wire bonding process after copperization of a silicon carbide power device chip. Background Art
[0002] Silicon carbide (SiC), as a typical representative of the third generation of wide bandgap semiconductor materials, has attracted much attention in the field of modern semiconductor technology because of its excellent characteristics such as wider bandgap (3.26eV), larger breakdown voltage, higher electron drift velocity and excellent thermal conductivity than silicon (Si) devices. These characteristics enable SiC devices to break through many limitations faced by traditional silicon devices in terms of switching speed, junction temperature and power density. In the field of power devices, the advantages of SiC devices are particularly significant. Its higher operating temperature and power density can not only greatly simplify the cooling system of the device, effectively reduce the complexity and volume of the system, but also reduce the weight of the power module to a certain extent, making the power module more flexible and lightweight in design and application. This trend of lightweight and miniaturization is of great significance for the development of modern electronic equipment towards high performance and portability. For example, in fields such as electric vehicles and aerospace that have strict requirements on the volume and weight of equipment, the application of SiC power devices can bring more optimization space for system design, improve energy efficiency and reduce overall costs.
[0003] The existing technology has certain defects. First, it is difficult to accurately control the thickness and uniformity of the coating when preparing the chip electrode layer. Wafer warping or insufficient buffering often occurs, and a stable electrical connection basis cannot be provided for the chip, affecting the chip reliability. Secondly, the traditional bonding technology parameters are not optimized enough, resulting in unstable bonding quality, frequent cold solder joints and desoldering, and mostly using aluminum wires, which have limited current carrying and heat dissipation capabilities, affecting the chip's electrical performance and power density improvement. Furthermore, conventional buffer layers are mostly single or simple composite structures with poor stress buffering effects. They cannot effectively disperse the bonding stress and are prone to causing internal damage to the chip, limiting the chip's damage resistance and overall stability improvement. To this end, we propose a copper wire bonding process after copperization of silicon carbide power device chips. Summary of the invention
[0004] The object of the present invention is to provide a copper wire bonding process after copperization of a silicon carbide power device chip.
[0005] In order to solve the problems raised in the above background technology, the present invention provides the following technical solution: a copper wire bonding process after copperization of a silicon carbide power device chip, the copper wire bonding process comprising the following specific steps:
[0006] Step 1: Chip pretreatment: prepare silicon carbide power device chips, place the chips in a cleaning tank, inject a volume of a chemical solvent mixed with acetone and ethanol to completely immerse the chips, start the ultrasonic cleaning equipment for cleaning, and use the impact force generated by ultrasonic cavitation to remove oil stains, particulate impurities and organic pollutants on the chip surface. Then, take the chip out of the cleaning tank, blow the chip surface with filtered dry nitrogen to remove residual solvent droplets, and finally transfer the chip to an oven for drying. Dry it for a period of time in a dry, static-free environment to ensure that the chip surface is thoroughly dry, clean, flat and free of impurities and defects.
[0007] Step 2: Electrode layer evaporation: The evaporation operation is performed on the chip surface in sequence. The nickel layer is firstly evaporated by electron beam evaporation process. The nickel source material is first placed in the evaporation source and evacuated. Then, the electron beam evaporator is turned on to deposit nickel atoms on the chip surface. Then, the metal palladium layer is evaporated by thermal evaporation process. Then, the metal copper layer is evaporated by magnetron sputtering process. Through the magnetron sputtering process, the copper target is installed on the sputtering cathode, so that the copper atoms are sputtered faster under the action of magnetic field and electric field and evenly deposited on the chip surface.
[0008] Step 3: Prepare a buffer layer, select polyimide and polyurethane as the basic materials of the buffer layer, and use a thermal evaporation deposition method to evacuate the deposition equipment according to the gradient structure from the electrode layer contact side to the copper wire contact side. During deposition, a polyimide starting layer is first deposited on the chip surface of the evaporated electrode layer, and finally a polyurethane surface layer is deposited to ensure that it can provide a good stress buffering effect when in contact with the copper wire;
[0009] Step 4: Prepare the copper wire by placing it in the reaction chamber of the plasma cleaning equipment, introducing oxygen after vacuuming, and then turning on the RF power supply to allow the oxygen plasma to react chemically with the surface of the copper wire to remove oxides and oil impurities on the surface, ensuring that the surface of the copper wire is clean to improve the subsequent bonding quality. After cleaning, take out the copper wire under the protection of inert gas argon to prevent re-oxidation;
[0010] Step 5: Copper wire bonding. Place the processed chip on the workbench of the bonding equipment. Use the hot-pressing ultrasonic bonding technology. First, heat up the bonding equipment, then apply bonding pressure, and turn on the ultrasonic generator for ultrasonic treatment. Continue bonding for a period of time to complete the copper wire bonding. Under the synergistic effect of heat, pressure, and ultrasound, the copper wire and the copper electrode layer on the surface of the chip form a firm bond, ensuring the formation of a good intermetallic compound to achieve reliable electrical connection, avoiding poor bonding and chip damage. During the bonding process, the stability of the bonding parameters is monitored by a real-time monitoring system to ensure the quality consistency of each bonding point.
[0011] Step 6: Post-processing and testing. After bonding is completed, the chip is transferred to a cleaning device and cleaned with a deionized water spray cleaning process to remove impurities, debris, and by-products that may be produced during the bonding process. After cleaning, the chip surface is dried with filtered dry nitrogen, and then the chip is fully tested to ensure that it meets the requirements.
[0012] As a further scheme of the present invention: in the step 1, the chemical solvent is a mixture of acetone and ethanol in a volume ratio of 3:1, the purity of acetone is 99.0%-99.5%, the purity of ethanol is 99.0%-99.7%, the ultrasonic cleaning equipment is set to an ultrasonic frequency of 40kHz, and the cleaning is continued for 8min-15min. The nitrogen purged from the surface of the chip needs to be filtered with a filter membrane with a pore size of 0.1μm-0.3μm, the temperature in the oven is controlled at 75°C-105°C, and the drying is carried out for 25min-65min.
[0013] As a further solution of the present invention: in the step 2, the thickness of the nickel layer is controlled to be 3 μm-5 μm when evaporating, and the nickel source material is placed in the evaporation source by electron beam evaporation process, and the vacuum is evacuated to 2×10 -4 Pa-5×10 -4 Pa high vacuum environment, turn on the electron beam evaporator, adjust the electron beam current to 100mA-200mA, and make nickel atoms evenly deposit on the chip surface at a rate of 0.1μm / min-0.2μm / min.
[0014] As a further solution of the present invention: in the step 2, the thickness of the deposited metal palladium layer is 0.5μm-1.5μm, and the crucible containing the palladium source material is heated to 1000℃-1200℃ using a thermal evaporation process, and the evaporation rate is adjusted to 0.05μm / min-0.1μm / min by controlling the heating power.
[0015] As a further solution of the present invention: in the step 2, the thickness of the evaporated metal copper layer is 15μm-25μm. Through the magnetron sputtering process, the copper target is installed on the sputtering cathode, and the vacuum is evacuated to 0.5Pa-1.0Pa and then argon gas is introduced. The argon gas flow rate is adjusted to 1.8L / min-3.0L / min, and the sputtering power is controlled at 100W-150W, so that the copper atoms are accelerated to sputter under the action of the magnetic field and electric field and are evenly deposited on the chip surface.
[0016] As a further solution of the present invention: in the step 3, the elastic modulus of the polyimide of the base material is 2GPa-5GPa, the elastic modulus of the polyurethane is 0.1GPa-1GPa, the mass ratio of the polyimide to the polyurethane from the electrode layer contact side to the copper wire contact side gradually transitions from 7:3 to 3:7, and the deposition equipment is first evacuated to 0.5×10-3 -1.0×10 -3 Pa, the temperature of the thermal evaporation source is controlled to be 130℃-270℃ during each layer deposition, the evaporation source power is adjusted to keep the deposition rate at 0.3nm / s-1.8nm / s, the total thickness of the buffer layer is set to 0.8μm-3.2μm, the thickness of the starting polyimide layer is 350nm-550nm, the thickness of the intermediate transition layer is 250nm-450nm, and the thickness of the polyurethane layer close to the copper wire is 80nm-220nm. During deposition, a polyimide starting layer is first deposited on the chip surface of the evaporated electrode layer, the evaporation source power is controlled to be 80W-160W and the evaporation time is 4min-12min, and finally the polyurethane surface layer is deposited, and the evaporation source power is controlled to be 40W-120W.
[0017] As a further solution of the present invention: in the step 4, the copper wire selected is a copper wire with a diameter of 12μm-32μm, the reaction chamber is evacuated to less than 8Pa-12Pa and then oxygen is introduced, the oxygen flow rate is adjusted to 15mL / min-35mL / min, and the RF power supply sets the RF power to 80W-180W.
[0018] As a further solution of the present invention: in the step five, the temperature of the bonding equipment is raised to 180°C-380°C, the welding pressure is 15N-50N, and a stepped ultrasonic power is adopted, the first stage is 50mW / 50ms, the second stage is 100mW / 100ms, the third stage is 120mW / 50ms, and the bonding time is 200ms.
[0019] As a further solution of the present invention: in the step six, a mild deionized water spray cleaning process with a spray pressure of 0.08MPa-0.22MPa and a spray time of 25s-65s is adopted in the cleaning device. After cleaning and drying, the chip is comprehensively tested. The specific tests are as follows: the on-resistance is measured by a micro-ohmmeter with an accuracy of 0.1mΩ using a four-wire measurement method, the insulation resistance is measured by an insulation resistance tester with a test voltage of 600V according to a standard test method, the bonding strength is tested by a tensile tester with a range of 0g-600g and an accuracy of 0.05g-0.2g to evaluate the firmness of the bonding point, and the appearance is comprehensively inspected with an optical microscope with a magnification of 40 times to 120 times to observe whether the bonding point has defects and whether the copper wire is broken and displaced.
[0020] By adopting the above technical solution, compared with the prior art, the beneficial effects of the present invention are:
[0021] 1. The present invention deposits a nickel layer, a metal palladium layer and a metal copper layer of a specific thickness and sequence on the chip surface, and prepares a buffer layer with a gradient structure. The precisely controlled electrode layer deposition process ensures the uniformity and appropriate thickness of the coating, avoids problems such as wafer warping and buffer failure, and provides a stable electrical connection basis for the chip. The gradient structure of the buffer layer can gradually reduce the elastic modulus from contact with the electrode layer to contact with the copper wire according to the stress distribution characteristics, greatly improving the stress dispersion effect. In the copper wire bonding process, the chip breakage problem caused by the high hardness of the copper wire can be effectively prevented, significantly improving the reliability of the chip during bonding and subsequent use, extending the service life of the chip, and reducing the risk of product failure caused by chip damage;
[0022] 2. The present invention ensures the formation of good intermetallic compounds between the copper wire and the copper electrode layer on the surface of the chip by adopting hot pressing ultrasonic bonding technology and optimizing bonding parameters, thereby achieving reliable electrical connection. During the bonding process, a suitable combination of bonding temperature, pressure, ultrasonic power and time parameters makes the quality consistency of the bonding points high, and reduces poor bonding phenomena such as cold soldering and desoldering. At the same time, compared with traditional aluminum wire bonding, the copper metallization on the chip surface and the use of copper wire improve the current carrying capacity, reduce the power loss of IGBT devices, and improve the heat dissipation capacity of the chip, thereby improving the power density of the module. This series of improvements enables the chip to transmit current more efficiently during operation, reduces the heat accumulation caused by poor electrical performance, and further improves the overall working stability and performance of the chip;
[0023] 3. The present invention brings significant advantages to the process through the unique gradient structure buffer layer design. The material elastic modulus gradually decreases from the contact side with the electrode layer to the contact side with the copper wire, which constructs a gradual stress buffer system. When the copper wire is bonded, the high elastic modulus part close to the electrode layer cooperates closely with the electrode layer to ensure the stability of the structure, while the low elastic modulus part close to the copper wire efficiently absorbs and disperses the stress peak transmitted from the copper wire. By accurately controlling the ratio of different materials such as polyimide and polyurethane and adopting a special layer-by-layer deposition process, the buffer layer structure is accurately constructed, overcoming the problem of limited stress buffering effect of conventional simple composite buffer layers, improving the damage resistance of the chip during the bonding process, reducing the probability of problems such as wafer damage, crater damage or pie l inside the chip due to stress concentration, and improving the overall reliability and stability of the chip. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A schematic diagram of the process steps in an embodiment of the present invention;
[0025] Figure 2 It is a schematic diagram for comparing performance parameters of embodiments of the present invention;
[0026] Figure 3 This is a schematic diagram of the bonding result of Example 1 in the embodiment of the present invention;
[0027] Figure 4 This is an overall schematic diagram of bonding in Example 1 of the embodiments of the present invention. DETAILED DESCRIPTION
[0028] The specific embodiments of the present invention will be further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention.
[0029] In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0030] Please refer to the attached Figure 1 -Attached Figure 4 The present invention provides a copper wire bonding process after copperization of a silicon carbide power device chip, and the copper wire bonding process includes the following specific steps:
[0031] Step 1: Chip pretreatment: prepare silicon carbide power device chips, place the chips in a cleaning tank, inject a volume of a chemical solvent mixed with acetone and ethanol to completely immerse the chips, start the ultrasonic cleaning equipment for cleaning, and use the impact force generated by ultrasonic cavitation to remove oil stains, particulate impurities and organic pollutants on the chip surface. Then, take the chip out of the cleaning tank, blow the chip surface with filtered dry nitrogen to remove residual solvent droplets, and finally transfer the chip to an oven for drying. Dry it for a period of time in a dry, static-free environment to ensure that the chip surface is thoroughly dry, clean, flat and free of impurities and defects.
[0032] Step 2: Electrode layer evaporation: The evaporation operation is performed on the chip surface in sequence. The nickel layer is firstly evaporated by electron beam evaporation process. The nickel source material is first placed in the evaporation source and evacuated. Then, the electron beam evaporator is turned on to deposit nickel atoms on the chip surface. Then, the metal palladium layer is evaporated by thermal evaporation process. Then, the metal copper layer is evaporated by magnetron sputtering process. Through the magnetron sputtering process, the copper target is installed on the sputtering cathode, so that the copper atoms are sputtered faster under the action of magnetic field and electric field and evenly deposited on the chip surface.
[0033] Step 3: Prepare a buffer layer, select polyimide and polyurethane as the basic materials of the buffer layer, and use a thermal evaporation deposition method to evacuate the deposition equipment according to the gradient structure from the electrode layer contact side to the copper wire contact side. During deposition, a polyimide starting layer is first deposited on the chip surface of the evaporated electrode layer, and finally a polyurethane surface layer is deposited to ensure that it can provide a good stress buffering effect when in contact with the copper wire;
[0034] Step 4: Prepare the copper wire by placing it in the reaction chamber of the plasma cleaning equipment, introducing oxygen after vacuuming, and then turning on the RF power supply to allow the oxygen plasma to react chemically with the surface of the copper wire to remove oxides and oil impurities on the surface, ensuring that the surface of the copper wire is clean to improve the subsequent bonding quality. After cleaning, take out the copper wire under the protection of inert gas argon to prevent re-oxidation;
[0035] Step 5: Copper wire bonding. Place the processed chip on the workbench of the bonding equipment. Use the hot-pressing ultrasonic bonding technology. First, heat up the bonding equipment, then apply bonding pressure, and turn on the ultrasonic generator for ultrasonic treatment. Continue bonding for a period of time to complete the copper wire bonding. Under the synergistic effect of heat, pressure, and ultrasound, the copper wire and the copper electrode layer on the surface of the chip form a firm bond, ensuring the formation of a good intermetallic compound to achieve reliable electrical connection, avoiding poor bonding and chip damage. During the bonding process, the stability of the bonding parameters is monitored by a real-time monitoring system to ensure the quality consistency of each bonding point.
[0036] Step 6: Post-processing and testing. After bonding is completed, the chip is transferred to a cleaning device and cleaned with a deionized water spray cleaning process to remove impurities, debris, and by-products that may be produced during the bonding process. After cleaning, the chip surface is dried with filtered dry nitrogen, and then the chip is fully tested to ensure that it meets the requirements.
[0037] In one embodiment of the present invention: in step 1, the chemical solvent is a mixture of acetone and ethanol in a volume ratio of 3:1, the purity of acetone is 99.0%-99.5%, the purity of ethanol is 99.0%-99.7%, the ultrasonic cleaning equipment is set to an ultrasonic frequency of 40kHz, and the cleaning is continued for 8min-15min. The nitrogen purged from the surface of the chip needs to be filtered with a filter membrane with a pore size of 0.1μm-0.3μm, the temperature in the oven is controlled at 75℃-105℃, and the drying is carried out for 25min-65min.
[0038] In one embodiment of the present invention, in step 2, the thickness of the nickel layer is controlled to be 3 μm-5 μm, and the nickel source material is placed in the evaporation source by electron beam evaporation process, and the vacuum is evacuated to 2×10 -4 Pa-5×10 -4 Pa high vacuum environment, turn on the electron beam evaporator, adjust the electron beam current to 100mA-200mA, and make nickel atoms evenly deposit on the chip surface at a rate of 0.1μm / min-0.2μm / min.
[0039] In one embodiment of the present invention: in step 2, the thickness of the deposited metal palladium layer is 0.5μm-1.5μm, and the crucible containing the palladium source material is heated to 1000℃-1200℃ using a thermal evaporation process, and the evaporation rate is adjusted to 0.05μm / min-0.1μm / min by controlling the heating power.
[0040] In one embodiment of the present invention: in step 2, the thickness of the evaporated metal copper layer is 15μm-25μm. Through the magnetron sputtering process, the copper target is installed on the sputtering cathode, and argon gas is introduced after evacuating to 0.5Pa-1.0Pa, and the argon gas flow rate is adjusted to 1.8L / min-3.0L / min. The sputtering power is controlled at 100W-150W, so that the copper atoms are accelerated to sputter under the action of the magnetic field and electric field and are evenly deposited on the chip surface.
[0041] In one embodiment of the present invention, in step 3, the elastic modulus of the polyimide of the base material is 2GPa-5GPa, the elastic modulus of the polyurethane is 0.1GPa-1GPa, and the mass ratio of the polyimide to the polyurethane from the electrode layer contact side to the copper wire contact side gradually transitions from 7:3 to 3:7. The deposition equipment is first evacuated to 0.5×10 -3 -1.0×10 -3 Pa, the temperature of the thermal evaporation source is controlled to be 130℃-270℃ during each layer deposition, the evaporation source power is adjusted to keep the deposition rate at 0.3nm / s-1.8nm / s, the total thickness of the buffer layer is set to 0.8μm-3.2μm, the thickness of the starting polyimide layer is 350nm-550nm, the thickness of the intermediate transition layer is 250nm-450nm, and the thickness of the polyurethane layer close to the copper wire is 80nm-220nm. During deposition, a polyimide starting layer is first deposited on the chip surface of the evaporated electrode layer, the evaporation source power is controlled to be 80W-160W and the evaporation time is 4min-12min, and finally the polyurethane surface layer is deposited, and the evaporation source power is controlled to be 40W-120W.
[0042] In one embodiment of the present invention: in step 4, the selected copper wire is a copper wire with a diameter of 12μm-32μm, the reaction chamber is evacuated to less than 8Pa-12Pa, and oxygen is introduced, the oxygen flow rate is adjusted to 15mL / min-35mL / min, and the RF power supply sets the RF power to 80W-180W.
[0043] In one embodiment of the present invention: in step five, the temperature of the bonding equipment is raised to 180°C-380°C, the welding pressure is 15N-50N, and a stepped ultrasonic power is used, the first stage is 50mW / 50ms, the second stage is 100mW / 100ms, the third stage is 120mW / 50ms, and the bonding time is 200ms.
[0044] In one embodiment of the present invention: In step six, a mild deionized water spray cleaning process with a spray pressure of 0.08MPa-0.22MPa and a spray time of 25s-65s is adopted in the cleaning device. After cleaning and drying, the chip is comprehensively tested. The specific tests are as follows: the on-resistance is measured by a micro-ohmmeter with an accuracy of 0.1mΩ using a four-wire measurement method, the insulation resistance is measured by an insulation resistance tester with a test voltage of 600V according to a standard test method, the bonding strength is tested by a tensile tester with a range of 0g-600g and an accuracy of 0.05g-0.2g to evaluate the firmness of the bonding point, and the appearance is comprehensively inspected with an optical microscope with a magnification of 40 times to 120 times to observe whether the bonding point has defects and whether the copper wire is broken and displaced.
[0045] In one embodiment of the present invention: In step one, during the ultrasonic cleaning process, a low-frequency vibration with a frequency of 10kHz-20kHz is simultaneously applied to the cleaning tank, and the low-frequency vibration forms a difference frequency effect with the ultrasonic cleaning frequency, further enhancing the removal effect of stubborn oil stains and impurities on the chip surface, and a rotatable tray is provided at the bottom of the ultrasonic cleaning equipment, and the tray rotation speed is 5r / min-10r / min, so that the chip can be evenly washed during the cleaning process, thereby improving the cleaning efficiency and quality.
[0046] In one embodiment of the present invention: in step 2, during the electrode layer evaporation process, an ion beam assist device is provided between the evaporation source and the chip, the ion beam energy is 50eV-150eV, and the ion beam current density is 10μA / cm 2 -30μA / cm 2 By bombarding atoms during the evaporation process with ion beams, the deposited atoms can obtain a higher mobility on the chip surface, thereby improving the density and adhesion of the coating and improving the quality of the electrode layer.
[0047] In one embodiment of the present invention: in the post-processing and detection process in step six, after the deionized water spray cleaning process, a plasma cleaning step is added, using a mixed gas of argon and hydrogen as a plasma source, wherein the argon flow rate is 20-30sccm, the hydrogen flow rate is 5-10sccm, the RF power is 100-200W, and the duration is 10-20 seconds, which is used to remove trace organic matter and particulate impurities remaining on the chip surface after deionized water cleaning, further improve the cleanliness of the chip surface, thereby improving the accuracy of detection and the performance of the chip.
[0048] Example 1, please refer to the attached Figure 1 -Attached Figure 4First, prepare the silicon carbide power device chip, place the chip in the cleaning tank, inject a chemical solvent mixed with acetone and ethanol in a volume ratio of 3:1, where the purity of acetone is 99.5% and the purity of ethanol is 99.7%, so that the chip is completely immersed, and start the ultrasonic cleaning equipment with an ultrasonic frequency of 40kHz for 15 minutes to remove oil, particulate impurities and organic pollutants on the chip surface. Then, blow the chip surface with dry nitrogen filtered with a pore size of 0.3μm, and then transfer the chip to a 105℃ oven for 65 minutes to ensure that the chip surface is dry, clean, flat and free of impurities and defects. Then, perform electrode layer evaporation. First, evaporate the nickel layer, place the nickel source material in the evaporation source, and evacuate to 5×10 -4 Pa, turn on the electron beam evaporator, adjust the electron beam current to 200mA, deposit nickel atoms at a rate of 0.2μm / min, control the nickel layer thickness to 5μm, then evaporate the metal palladium layer, heat the crucible containing the palladium source material to 1200℃, adjust the evaporation rate to 0.1μm / min by controlling the heating power, make the palladium layer thickness reach 1.5μm, then evaporate the metal copper layer, install the copper target on the sputtering cathode, evacuate to 1.0Pa and then introduce argon gas, adjust the argon gas flow rate to 3.0L / min, control the sputtering power at 150W, deposit copper atoms, and the copper layer thickness is 25μm. Then prepare the buffer layer, select polyimide with an elastic modulus of 5GPa and polyurethane with an elastic modulus of 1GPa as the basic materials, design a gradient structure with a mass ratio of polyimide to polyurethane gradually transitioning from 7:3 to 3:7 from the electrode layer contact side to the copper wire contact side, and use the thermal evaporation deposition method. First, evacuate the deposition equipment to 1.0×10 -3 Pa, the temperature of the thermal evaporation source was controlled to be 270 ° C during each layer deposition, the evaporation source power was adjusted to keep the deposition rate at 1.8nm / s, the total thickness of the buffer layer was set to 3.2μm, the initial polyimide layer thickness was 550nm, the evaporation source power was 160W, the evaporation time was 12 minutes, the intermediate transition layer thickness was 450nm, and the polyurethane layer thickness close to the copper wire was 220nm (the evaporation source power was 120W when depositing the surface layer). After that, the copper wire was prepared, a copper wire with a diameter of 32μm was selected, and placed in the reaction chamber of the plasma cleaning equipment. After evacuating to 12Pa, oxygen was introduced and the oxygen flow rate was adjusted to 3 5mL / min, the RF power supply is set to 180W. After cleaning for 12 minutes, it is taken out under argon protection to prevent re-oxidation. Finally, copper wire bonding is performed. The treated chip is placed on the bonding equipment workbench, the bonding equipment temperature is raised to 380℃, the welding pressure is 50N, and the stepped ultrasonic power is used. The first stage is 50mW / 50ms, the second stage is 100mW / 100ms, and the third stage is 120mW / 50ms. The bonding time is 200ms, so that the copper wire is firmly bonded to the copper electrode layer on the chip surface. The bonding process is monitored by a real-time monitoring system to monitor parameter stability.
[0049] Example 2, please refer to the attached Figure 1 -Attached Figure 4 First, prepare the silicon carbide power device chip, place the chip in the cleaning tank, inject a chemical solvent mixed with acetone and ethanol in a volume ratio of 3:1, where the purity of acetone is 99.0% and the purity of ethanol is 99.0%, so that the chip is completely immersed, and start the ultrasonic cleaning equipment with an ultrasonic frequency of 25kHz for 8 minutes to remove oil, particulate impurities and organic pollutants on the chip surface. Then, blow the chip surface with nitrogen, and then transfer the chip to a 75℃ oven for 25 minutes to ensure that the chip surface is dry, clean, flat and free of impurities and defects. Then, perform electrode layer evaporation. First, evaporate the nickel layer, place the nickel source material in the evaporation source, and evacuate to 2×10 -4 Pa, turn on the electron beam evaporator, adjust the electron beam current to 100mA, deposit nickel atoms at a rate of 0.1μm / min, control the nickel layer thickness to 3μm, then evaporate the metal palladium layer, heat the crucible containing the palladium source material to 1000℃, adjust the evaporation rate to 0.05μm / min by controlling the heating power, make the palladium layer thickness reach 0.5μm, then evaporate the metal copper layer, install the copper target on the sputtering cathode, evacuate to 0.5Pa and then introduce argon gas, adjust the argon gas flow rate to 1.8L / min, control the sputtering power at 100W, deposit copper atoms, and the copper layer thickness is 15μm. Then prepare the buffer layer, select polyimide with an elastic modulus of 2GPa and polyurethane with an elastic modulus of 0.1GPa as the basic materials, design a gradient structure with a mass ratio of polyimide to polyurethane gradually transitioning from 7:3 to 3:7 from the electrode layer contact side to the copper wire contact side, and use thermal evaporation deposition method, first evacuate the deposition equipment to 0.5×10 -3 Pa, the temperature of the thermal evaporation source was controlled to be 130°C during each layer deposition, the evaporation source power was adjusted to keep the deposition rate at 0.3nm / s, the total thickness of the buffer layer was set to 0.8μm, the initial polyimide layer thickness was 350nm, the evaporation source power was 80W, the evaporation time was 4 minutes, the intermediate transition layer thickness was 250nm, and the polyurethane layer thickness close to the copper wire was 80nm (the evaporation source power was 40W when depositing the surface layer). After that, the copper wire was prepared, a copper wire with a diameter of 12μm was selected, placed in the reaction chamber of the plasma cleaning equipment, and oxygen was introduced after evacuating to 8Pa. , adjust the oxygen flow rate to 15mL / min, set the RF power to 80W, take it out under argon protection after cleaning for 4 minutes to prevent re-oxidation, and finally perform copper wire bonding. Place the treated chip on the bonding equipment workbench, raise the bonding equipment temperature to 180℃, and use a stepped ultrasonic power of 50mW / 50ms in the first stage, 100mW / 100ms in the second stage, and 120mW / 50ms in the third stage. The bonding time is 200ms to firmly bond the copper wire to the copper electrode layer on the chip surface.
[0050] Example 3, please refer to the attached Figure 1 -Attached Figure 4 First, prepare the silicon carbide power device chip and perform electrode layer evaporation. First, evaporate the nickel layer. Place the nickel source material in the evaporation source and evacuate it to 2×10 -4 Pa, turn on the electron beam evaporator, adjust the electron beam current to 100mA, deposit nickel atoms at a rate of 0.1μm / min, control the nickel layer thickness to 3μm, then evaporate the metal palladium layer, heat the crucible containing the palladium source material to 1000℃, adjust the evaporation rate to 0.05μm / min by controlling the heating power, make the palladium layer thickness reach 0.5μm, then evaporate the metal copper layer, install the copper target on the sputtering cathode, evacuate to 0.5Pa and then introduce argon gas, adjust the argon gas flow rate to 1.8L / min, control the sputtering power at 100W, deposit copper atoms, and the copper layer thickness is 15μm. Then prepare the buffer layer, select polyimide with an elastic modulus of 2GPa and polyurethane with an elastic modulus of 0.1GPa as the basic materials, design a gradient structure with a mass ratio of polyimide to polyurethane gradually transitioning from 7:3 to 3:7 from the electrode layer contact side to the copper wire contact side, and use thermal evaporation deposition method, first evacuate the deposition equipment to 0.5×10 -3 Pa, the temperature of the thermal evaporation source was controlled to be 130°C during each layer deposition, the evaporation source power was adjusted to keep the deposition rate at 0.3nm / s, the total thickness of the buffer layer was set to 0.8μm, the initial polyimide layer thickness was 350nm, the evaporation source power was 80W, the evaporation time was 4 minutes, the intermediate transition layer thickness was 250nm, and the polyurethane layer thickness close to the copper wire was 80nm (the evaporation source power was 40W when depositing the surface layer). After that, the copper wire was prepared, a copper wire with a diameter of 300μm was selected, placed in the reaction chamber of the plasma cleaning equipment, and oxygen was introduced after evacuating to 8Pa. , adjust the oxygen flow rate to 15mL / min, set the RF power of the RF power supply to 80W, take it out under argon protection after cleaning for 4 minutes to prevent re-oxidation, and finally perform copper wire bonding. Place the treated chip on the bonding equipment workbench, raise the bonding equipment temperature to 250℃, and the welding pressure is 35N. Use stepped ultrasonic power, the first stage is 50mW / 50ms, the second stage is 100mW / 100ms, and the third stage is 120mW / 50ms. The bonding time is 200ms, so that the copper wire is firmly bonded to the copper electrode layer on the surface of the chip.
[0051] Designing the Experiment
[0052] Experimental materials: 30 groups of silicon carbide power device chips were taken and divided into 3 groups, each with 10 parts, which were used for the process treatments of Example 1, Example 2 and Example 3 respectively; acetone and ethanol were used as cleaning solvents for chip pretreatment; metal materials such as nickel, palladium, and copper were used as raw materials for electrode layer evaporation; polyimide (PI) and polyurethane (PU) materials were used for buffer layer preparation; copper wires with diameters of 32 μm and 12 μm, ultrasonic cleaning equipment, electron beam evaporation equipment, thermal evaporation equipment, magnetron sputtering equipment, plasma cleaning equipment, bonding equipment, and various testing instruments (microohmmeter, insulation resistance tester, tensile tester, optical microscope, stress sensor, etc.);
[0053] Experimental procedures
[0054] Sample grouping and processing
[0055] The prepared silicon carbide power device chips are evenly divided into three groups, which are marked as group one (corresponding to embodiment one), group two (corresponding to embodiment two), and group three (corresponding to embodiment three). According to the process requirements of each embodiment, the three groups of chips are respectively subjected to a complete processing flow, including chip pre-processing, electrode layer evaporation, buffer layer preparation, copper wire preparation, copper wire bonding, and post-processing and testing. In each step, the process parameters specified in each embodiment are strictly controlled for operation;
[0056] Data collection
[0057] Chip reliability and damage resistance:
[0058] The three groups of chips were placed in a composite environmental test box with high temperature, high humidity, vibration, etc., which simulates the actual use environment. The high temperature was set to 150°C, the high humidity was set to 90%RH, the vibration frequency was set to 50Hz, and the vibration acceleration was set to 2g. The duration was 100 hours. Each group of chips was subjected to such environmental tests 10 times. After each test, the number of chips that were damaged (electrical performance failure, physical structure damage, etc.) was counted, and the damage rate of each test was calculated (the number of damaged chips ÷ the total number of chips × 100%). Finally, the average of the 10 damage rates was taken as the average damage rate of the group of chips in this environment.
[0059] A certain external force impact is applied to the three groups of chips respectively. A drop hammer impact test equipment can be used. The drop hammer height is set to 50 cm. The impact energy is calculated and determined according to factors such as chip size and mass (according to the formula E=mgh, where m is the chip mass, g is the acceleration of gravity, and h is the drop hammer height). The impact point is selected at the key part of the chip. Each group of chips is subjected to 10 impact tests. After each impact, the number of broken chips is counted, and the breakage rate of each test is calculated (the number of broken chips ÷ the total number of chips × 100%). Finally, the average of the 10 breakage rates is taken as the average breakage rate of the group of chips under the impact condition;
[0060] Bonding quality and electrical performance:
[0061] On-resistance detection: Use a micro-ohmmeter with an accuracy of 0.1mΩ to measure each group of chips using a four-wire measurement method. Randomly select 10 measurement points for each group of chips, read the on-resistance value of each measurement point, and finally take the average of these measurement values as the average on-resistance value of the group of chips. Insulation resistance detection: Use an insulation resistance tester with a test voltage of 600V to measure each group of chips according to the standard test method. Similarly, select 10 measurement points for each group of chips, record the insulation resistance value of each measurement point, and take the average value as the average insulation resistance value of the group of chips;
[0062] Bond strength test: Use a tensile tester with a range of 0-600g and an accuracy of 0.05-0.2g to perform a tensile test on the 10 bonding points of each group of chips, record the maximum tensile value displayed by the tensile tester when each bonding point is broken, and finally take the average of these tensile values as the average bonding strength value of the group of chips;
[0063] Buffer layer stress buffering effect:
[0064] During the copper wire bonding process of the chip, a stress sensor is used to measure the stress magnitude at different positions on the chip surface. The stress sensor is pasted on the predetermined bonding point on the chip surface and at the junction of the buffer layer and the electrode layer. The stress data is recorded in real time during the bonding process. Each group of chips undergoes stress measurement during the bonding process 5 times. After each measurement, the stress peak value is obtained through data processing and analysis. Finally, the average value of the 5 stress peak values is taken as the average stress peak value of the group of chips during the bonding process. The three groups of chips are subjected to 100 thermal cycle tests respectively. The thermal cycle temperature range is set to -40°C to 125°C. Each thermal cycle includes a process from low temperature to high temperature and then back to low temperature. The heating rate and cooling rate are both controlled at 5°C / min. After the thermal cycle, an optical microscope is used to carefully observe whether there is wafer damage, crater damage or pie l inside the chip. The observation results of each group of chips are statistically analyzed, the number of chips with the above problems is recorded, and the proportion of chips with problems to the total number of chips in the group is calculated as the damage proportion of the group of chips after thermal cycling.
[0065] As attached Figure 2As shown, through the analysis of the experimental data, it can be seen that in terms of chip reliability and damage resistance, the average chip damage rate (1.2%) and breakage rate (1.8%) of Example 1 are lower than those of Example 2 (3.5%, 4.2%) and Example 3 (4.0%, 4.8%), indicating that Example 1 can better protect the chip. In terms of bonding quality and electrical performance, the average on-resistance (0.82mΩ) of Example 1 is lower, and the average bonding strength (145.2g) is higher, which is higher than that of Example 2 (1.23mΩ, 102.5 g) and Example 3 (1.31mΩ, 98.3g), its electrical connection and bonding firmness are better. For the stress buffering effect of the buffer layer, the average stress peak value (45.2N) of Example 1 is smaller than that of Example 2 (72.3N) and Example 3 (78.7N), and the damage ratio after thermal cycling (8.2%) is also lower than that of Example 2 (18.3%) and Example 3 (22.5%), indicating that its buffer layer has a better stress dispersion effect and reduces chip damage. Overall, Example 1 performs best in terms of the three beneficial effects.
[0066] Although the present invention is disclosed as above in terms of preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, any modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention shall fall within the scope of protection defined by the claims of the present invention.
Claims
1. A copper wire bonding process after copperization of silicon carbide power device chip, characterized in that: The copper wire bonding process includes the following specific steps: Step 1: Chip pretreatment: prepare silicon carbide power device chips, place the chips in a cleaning tank, inject a volume of a chemical solvent mixed with acetone and ethanol to completely immerse the chips, start the ultrasonic cleaning equipment for cleaning, then take the chips out of the cleaning tank, purge the chip surface with filtered dry nitrogen, and finally transfer the chips to an oven for drying, and dry them for a period of time in a dry, static-free environment; Step 2: Electrode layer evaporation: perform evaporation operations on the chip surface in sequence. First, use electron beam evaporation to evaporate the nickel layer. First, place the nickel source material in the evaporation source and evacuate it. Then, turn on the electron beam evaporator to deposit nickel atoms on the chip surface. Then, use the thermal evaporation process to evaporate the metal palladium layer. Then, use the magnetron sputtering process to evaporate the metal copper layer. Through the magnetron sputtering process, install the copper target on the sputtering cathode. Step 3: Prepare a buffer layer, select polyimide and polyurethane as the basic materials of the buffer layer, and use a thermal evaporation deposition method to evacuate the deposition equipment according to the gradient structure from the electrode layer contact side to the copper wire contact side. During deposition, a polyimide starting layer is first deposited on the chip surface of the evaporated electrode layer, and finally a polyurethane surface layer is deposited; Step 4: Prepare the copper wire by placing it in the reaction chamber of the plasma cleaning equipment, introducing oxygen after vacuuming, and then turning on the radio frequency power supply to allow the oxygen plasma to react chemically with the surface of the copper wire. After the cleaning is completed, the copper wire is taken out under the protection of the inert gas argon; Step 5: Copper wire bonding: Place the processed chip on the bonding equipment workbench, use hot pressing ultrasonic bonding technology, first heat up the bonding equipment, then apply bonding pressure, and turn on the ultrasonic generator for ultrasonic treatment, and continue bonding for a period of time to complete the copper wire bonding; Step 6: Post-processing and testing. After bonding is completed, the chip is transferred to a cleaning device and cleaned using a deionized water spray cleaning process. After cleaning, the chip surface is blown dry with filtered dry nitrogen gas, and then the chip is fully tested to ensure that the chip meets the requirements.
2. A copper wire bonding process after copperization of a silicon carbide power device chip according to claim 1, characterized in that: In the step 1, the chemical solvent is a mixture of acetone and ethanol in a volume ratio of 3:1, the purity of acetone is 99.0%-99.5%, the purity of ethanol is 99.0%-99.7%, the ultrasonic cleaning equipment is set to an ultrasonic frequency of 40kHz, and the cleaning is continued for 8min-15min. The nitrogen purged on the surface of the chip needs to be filtered with a filter membrane with a pore size of 0.1μm-0.3μm, the temperature in the oven is controlled at 75°C-105°C, and the drying is carried out for 25min-65min.
3. The copper wire bonding process after copperization of silicon carbide power device chip according to claim 1, characterized in that: In the step 2, the thickness of the nickel layer is controlled to be 3 μm-5 μm when evaporating the nickel layer. The nickel source material is placed in the evaporation source by electron beam evaporation process and vacuumed to 2×10 -4 Pa-5×10 -4 Pa high vacuum environment, turn on the electron beam evaporator, adjust the electron beam current to 100mA-200mA, and make nickel atoms evenly deposit on the chip surface at a rate of 0.1μm / min-0.2μm / min.
4. The copper wire bonding process after copperization of silicon carbide power device chip according to claim 1, characterized in that: In the step 2, the thickness of the deposited metal palladium layer is 0.5 μm-1.5 μm, and the crucible containing the palladium source material is heated to 1000° C.-1200° C. using a thermal evaporation process, and the evaporation rate is adjusted to 0.05 μm / min-0.1 μm / min by controlling the heating power.
5. The copper wire bonding process after copperization of silicon carbide power device chip according to claim 1, characterized in that: In the step 2, the thickness of the evaporated metal copper layer is 15 μm-25 μm. The copper target is installed on the sputtering cathode through the magnetron sputtering process. After evacuating to 0.5Pa-1.0Pa, argon gas is introduced, and the argon gas flow rate is adjusted to 1.8L / min-3.0L / min. The sputtering power is controlled at 100W-150W.
6. A copper wire bonding process after copperization of a silicon carbide power device chip according to claim 1, characterized in that: In the step 3, the elastic modulus of the polyimide of the base material is 2GPa-5GPa, the elastic modulus of the polyurethane is 0.1GPa-1GPa, and the mass ratio of polyimide to polyurethane from the electrode layer contact side to the copper wire contact side gradually transitions from 7:3 to 3:
7. The deposition equipment is first evacuated to 0.5×10 -3 -1.0×10 -3 Pa, the temperature of the thermal evaporation source is controlled to be 130℃-270℃ during each layer deposition, the evaporation source power is adjusted to keep the deposition rate at 0.3nm / s-1.8nm / s, the total thickness of the buffer layer is set to 0.8μm-3.2μm, the thickness of the starting polyimide layer is 350nm-550nm, the thickness of the intermediate transition layer is 250nm-450nm, and the thickness of the polyurethane layer close to the copper wire is 80nm-220nm. During deposition, a polyimide starting layer is first deposited on the chip surface of the evaporated electrode layer, the evaporation source power is controlled to be 80W-160W and the evaporation time is 4min-12min, and finally the polyurethane surface layer is deposited, and the evaporation source power is controlled to be 40W-120W.
7. A copper wire bonding process after copperization of a silicon carbide power device chip according to claim 1, characterized in that: In the step 4, the copper wire selected is a copper wire with a diameter of 12 μm-32 μm, the reaction chamber is evacuated to less than 8Pa-12Pa, and oxygen is introduced, the oxygen flow rate is adjusted to 15mL / min-35mL / min, and the RF power supply is set to 80W-180W.
8. The copper wire bonding process after copperization of silicon carbide power device chip according to claim 1, characterized in that: In the step five, the temperature of the bonding equipment is raised to 180°C-380°C, the welding pressure is 15N-50N, and a stepped ultrasonic power is used, with the first stage being 50mW / 50ms, the second stage being 100mW / 100ms, and the third stage being 120mW / 50ms, and the bonding time is 200ms.
9. A copper wire bonding process after copperization of a silicon carbide power device chip according to claim 1, characterized in that: In the step six, a mild deionized water spray cleaning process with a spray pressure of 0.08MPa-0.22MPa and a spray time of 25s-65s is adopted in the cleaning device. After cleaning and drying, the chip is comprehensively tested. The specific tests are as follows: the on-resistance is measured by a micro-ohmmeter with an accuracy of 0.1mΩ using a four-wire measurement method, the insulation resistance is measured by an insulation resistance tester with a test voltage of 600V according to a standard test method, the bond strength is tensile tested by a tensile tester with a range of 0g-600g and an accuracy of 0.05g-0.2g, and the appearance is inspected by an optical microscope with a magnification of 40 times to 120 times.
Citation Information
Cited By
Farm power grid regulation and control method and system adapting to off-line-on-line environment deviation
CN121939528A
Processing technology of optical waveguide structure and preparation method of optical waveguide sheet
CN122018072A
Optical waveguide structure, optical waveguide sheet, lens and AR glasses
CN122043648A
Silicon carbide optical waveguide structure, silicon carbide optical waveguide sheet, lens and AR glasses
CN122043649A